Separation and Immobilization of Vanadium from Industrial Fly Ash as an Insoluble Inorganic Pigment - P. Kwolek; K. Czubajewski; M. Wojnicki (Archives of Metallurgy and Materials, 2020)
It has been shown that the precipitation of bismuth orthovanadate from a fly ash leachate is a promising method of vanadium recovery. BiVO4 obtained after appropriate heat treatment can be sold as a pigment. The yield of recovery of solubilised vanadium is equal to 68% and the precipitate is free from nickel impurity. The precipitate is insoluble in the solutions with pH ≥ 3. In more acidic media the solubility of precipitate increases with the decreasing pH. The solubility of the precipitate increases also with the increasing concentration of chloride ions.